Fluoro-Aryl Substituted α,β2,3-Peptides in the Development of Foldameric Antiparallel β-Sheets: A Conformational Study - Bucci, Raffaella; Contini, Alessandro; Clerici, Francesca; Beccalli, Egle Maria; Formaggio, Fernando; Maffucci, Irene; Pellegrino, Sara; Gelmi, Maria Luisa (Frontiers in Chemistry, 2019)
α,β2,3-Disteroisomeric foldamers of general formula Boc(S-Ala-β-2R,3R-Fpg)nOMe or Boc(S-Ala-β-2S,3S-Fpg)nOMe were prepared from both enantiomers of syn H-2-(2-F-Phe)-h-PheGly-OH (named β-Fpg) and S-alanine. Our peptides show two appealing features for biomedical applications: the presence of fluorine, attractive for non-covalent interactions, and aryl groups, crucial for π-stacking. A conformational study was performed, using IR, NMR and computational studies of diastereoisomeric tetra- and hexapeptides containing the β2,3-amino acid in the R,R- and S,S-stereochemistry, respectively. We found that the stability of peptide conformation is dependent on the stereochemistry of the β-amino acid. Combining S-Ala with β-2R,3R-Fpg, a stable extended β-strand conformation was obtained. Furthermore, β-2R,3R-Fpg containing hexapeptide self-assembles to form antiparallel β-sheet structure stabilized by intermolecular H-bonds and π,π-interactions. These features make peptides containing the β2,3-fluoro amino acid very appealing for the development of bioactive proteolytically stable foldameric β-sheets as modulators of protein-protein interaction (PPI).